SALE OF ORGANIC FOOD IN SPECIALIST AND GENERAL RETAIL GROCERY OUTLETS - A COMPARATIVE ANALYSIS - Smoluk-Sikorska, Joanna; Łuczka-Bakuła, Władysława (Acta Scientiarum Polonorum. Oeconomia, 2013)
The article presents the results of an inquiry research carried out in 2011 among specialist and general retail grocery outlets offering organic food. A comparative analysis of the width and depth of organic products range was conducted and grounds for lack of the offer complexity, particularly in retail grocery outlets, were presented as well. The sources of supply in basic products groups and the distance to supplier as the factors determining the offer were discussed. The conducted research proves that the product range, especially in general retail outlets, is not sufficient, which results from the offer of the intermediate links of the organic food distribution channels and the relatively long distance to suppliers.